2010
DOI: 10.1017/s0144686x10000152
|View full text |Cite
|
Sign up to set email alerts
|

Filling a missing link: the influence of portrayals of older characters in television commercials on the memory performance of older adults

Abstract: The portrayal of older characters in television commercials has over time become more varied and positive. This study examines how different portrayals of older characters relate to self-stereotyping, a process through which older individuals apply their beliefs about older people in general to themselves and behave accordingly. The study thereby seeks to connect, as few have previously done, cultural studies and critiques of media portrayals with psychological studies of the effects of self-stereotyping. Sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
0
9
0
2
Order By: Relevance
“…These images are gendered as a consequence of the greater emphasis on physical appearance for women, and the representation of ageing bodies as at odds with norms of attractive femininity (Twigg 2004 ;Woodward 1991). It has been argued, however, that consumer culture is creating more positive representations of older people as active, healthy, independent and youthful (Katz 2001 ;Katz and Marshall 2003;Westerhof et al 2010), but those in ill-health and the ' oldest old ' may be unable to attain such images (Featherstone and Hepworth 1991). In such cases, online interactions offer possibilities for creating new images of the ageing body, and for escaping the negative judgements based on its outward appearance (Featherstone 1995).…”
Section: Ageing Bodies and Computer Usementioning
confidence: 99%
“…These images are gendered as a consequence of the greater emphasis on physical appearance for women, and the representation of ageing bodies as at odds with norms of attractive femininity (Twigg 2004 ;Woodward 1991). It has been argued, however, that consumer culture is creating more positive representations of older people as active, healthy, independent and youthful (Katz 2001 ;Katz and Marshall 2003;Westerhof et al 2010), but those in ill-health and the ' oldest old ' may be unable to attain such images (Featherstone and Hepworth 1991). In such cases, online interactions offer possibilities for creating new images of the ageing body, and for escaping the negative judgements based on its outward appearance (Featherstone 1995).…”
Section: Ageing Bodies and Computer Usementioning
confidence: 99%
“…Research has confirmed that both of these theories are accurate in that the media has an influence on how older people regard themselves (Donlon, Ashman and Levy 2005; Korzenny and Neuendorf 1980; Mares and Cantor 1992) and how they are regarded by younger people (Gerbner et al 1980; Passuth and Cook 1985). In addition, research has shown that self-stereotyping of older people can even lead to negative physiological effects such as impaired memory performance (Westerhof et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Still other studies showed that perceptions of older viewers on how they were represented by the advertiser influenced their purchase intentions as well as their overall view of the company image (Festervand & Lumpkin, 1985; Kolbe & Burnett, 1992; Prieler & Kohlbacher, 2016). In addition, research has shown that self-stereotyping of older people can even lead to negative physiological effects, such as impaired memory performance (Westerhof, Harink, Van Selm, Strick, & Van Baaren, 2010).…”
Section: Theoretical Frameworkmentioning
confidence: 99%